(untitled) (Physical Education, Health and Social Sciences, 2025)
Hypertension is recognized as one of the leading contributors to kidney damage. Additional factors such as diabetes, fluid deficiency, infections, inherited renal disorders, or certain environmental exposures can also cause kidney dysfunction in people who do not have high blood pressure. A reliable method for detecting reduced filtration capacity is to evaluate kidney performance through tests such as serum creatinine, blood urea, and estimated glomerular filtration rate (eGFR). The aim of this study was to investigate kidney dysfunction in hypertensive and non-hypertensive patients. This case control study was conducted at Mughal Labs Lahore, over the period of six months. A total of 80 patients aged from pediatric to geriatric years. Blood samples are collected and analyzed to check the kidney dysfunction (Blood Urea, Serum Creatinine and eGFR) using photometric method. Statistical analysis was performed using IBM SPSS 26, with continuous variables expressed as mean ± SD, and comparative analysis graphs. The study analyzed urea, creatinine, and eGFR using SPSS, comparing hypertensive and non-hypertensive groups with a t-test (p < 0.05). The mean kidney parameters were: blood urea (52±41mg/dL), serum creatinine (13±2mg/dL), eGFR (64±39mg/dL). 40 patient’s patients had indicated impaired kidney function, indicated by high serum creatinine and low eGFR with hypertension. 20 patients had normal renal function which means that 5 were hypertensive (6.25%) and 15 were non hypertensive (18.75%). The remaining 20 patients were non hypertensive but still showed sign of kidney function impairment due to other causes. The study highlights high blood pressure as an important and preventable contributor to renal damage. Lowering the impact of chronic kidney disease and improving long-term health results require timely detection through regular kidney function assessments and proper management of blood pressure.